New biomaterials for Ni biosorption turned into catalysts for Suzuki–Miyaura cross coupling of aryl iodides in green conditions. Issue 45 (19th August 2021) - Cases, Lucie; Adler, Pauline; Pelissier, Franck; Diliberto, Sébastien; Boulanger, Clotilde; Grison, Claude
Abstract : New biomaterials were functionalised for biosorption of Ni from aqueous solutions and valorised as ecocatalysts in Suzuki–Miyaura green reactions. Abstract : In parallel with increasing Ni production and utilisation, Ni pollution in the soil–water continuum has become an alarming and global problem. Solutions for removing Ni from industrial effluents have been widely investigated and biosorption has emerged as an efficient, cost-effective, scalable and sustainable alternative for water treatment. However, the biosorption capacity is limited by the chemical composition of the biomaterial and the Ni-enriched biomaterials are rarely valorised. In this work, the biosorption capacity of three abundant biomaterials with different chemical properties – water hyacinth, coffee grounds and pinecones – was studied before and after functionalization, and reached a maximum biosorption capacity of 51 mg g −1 of Ni(ii ). A bioinspired functionalization approach was investigated introducing carboxylate moieties and was conducted in green conditions. The Ni-enriched biomaterials were valorised by transformation into catalysts, which were characterised by MP-AES and XRPD. Their characterisation revealed a structure similar to nickel formate, and hence the Eco-Ni(HCOO)2 catalysts were tested in Suzuki–Miyaura reactions. Several aryl iodides were successfully cross-coupled to phenylboronic acids using Eco-Ni(HCOO)2 without any ligand, a mild and green base in a mixture of green solvents.